SURROGACY IN MUMBAI: REGULATION, PRACTICE, AND THE DYNAMICS OF ALTRUISTIC MODELS - Vyas, Varsha D.; Kaur, Mandeep; Kaur, Arshi Pal (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the impact of India’s shift to altruistic-only surrogacy under the Surrogacy (Regulation) Act, 2021 and the ART (Regulation) Act, 2021, including the 2024 donor gamete amendment, on surrogacy outcomes in Mumbai, a major ART hub. A mixed-methods approach combines clinic-level quantitative data and in-depth qualitative interviews with surrogates, intending parents, and clinic professionals. Findings reveal that registered clinics demonstrate higher compliance with documentation and insurance, while non-registered clinics show significant gaps. Donor gamete approvals increased marginally, but strict eligibility criteria continue to restrict access for diverse family forms. Surrogates report limited awareness of contracts, and intended parents face procedural delays, sometimes prompting informal surrogacy arrangements. Policy recommendations emphasize transparency, surrogate empowerment, inclusive access, and regulatory streamlining.